PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX1 SMP NEGERI 22 PEKANBARU - Yola, Nike Marta Yola Marta; Heleni, Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The results of that study are expected by every high school and achieve minimum mastery criteria. Lack of student learning outcomes are influenced by many factors. One is the learning prosess in the classroom. The research is classroom action research that aims to improve learning process and mathematics achievement with applied the approuch model of Think Pair Square. The subject of this research is student of class IX1 SMP Negeri 22 Pekanbaru in the first semester academic years 2014/2015, there are 32 students in the class, consist of 12 boys and 20 girls. The research are two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. At the end of each cycle, daily tests are carried out. Data collected through observation and tests in the form of daily tests. Observation is used to collect teacher and student activities during learning process, test is used to collect mathematic outcomes and will given in form daily test. The results show the activity of teachers and students in learning has been in line with the lesson plan and increase in students from the base score with the percentage 15,63% to 37,5 % on the first daily test and 71,88% on the second daily test. Results of this research indicate that the application of Structural Approach to Cooperative Learning Model Think Pair Square can improve learning process and improve the mathematics learning outcomes math class IX1 SMP Negeri 22 Pekanbaru in the first semester academic years 2014/2015. Keywords: Mathematics Learning Outcome, Cooperatif Learning Model Structural Approach of Think Pair Square, Class Action Research